2010
DOI: 10.1016/j.neulet.2010.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evidence of thermal hyperalgesia and mechanical allodynia induced by intradermal cinnamaldehyde in rats

Abstract: TRPA1 agonists cinnamaldehyde (CA) and mustard oil (allyl isothiocyanate= AITC) induce heat hyperalgesia and mechanical allodynia in human skin, and sensitize responses of spinal and trigeminal dorsal horn neurons to noxious skin heating in rats. TRPA1 is also implicated in cold nociception. We presently used behavioral methods to investigate if CA affects sensitivity to thermal and mechanical stimuli in rats. Unilateral intraplantar injection of CA (5-20%) induced a significant, concentration-dependent reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
5
28
2
Order By: Relevance
“…These discrepancies regarding the effects of CA on cold pain perception and neuronal responses may partly involve the route of delivery and accessibility of CA to intradermal nociceptors. In our preliminary investigation [58] and in the present study, intradermal injection of CA allowed for a direct access to nociceptive nerve endings, resulting in significant cold hyperalgesia and enhancement of cold avoidance.…”
Section: Discussionsupporting
confidence: 50%
“…These discrepancies regarding the effects of CA on cold pain perception and neuronal responses may partly involve the route of delivery and accessibility of CA to intradermal nociceptors. In our preliminary investigation [58] and in the present study, intradermal injection of CA allowed for a direct access to nociceptive nerve endings, resulting in significant cold hyperalgesia and enhancement of cold avoidance.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, several groups have shown that during inflammation, spinal TRPV1 receptors contribute significantly to both tactile allodynia and thermal hyperalgesia, but TRPV1 on peripheral terminals preferentially mediates the latter (7,(37)(38)(39). Peripheral activation of TRPA1 produces some thermal hyperalgesia, but the resulting tactile allodynia is the more robust response (40). Thus, the current work demonstrates that spinal HXA 3 contributes to the development of inflammatory hyperalgesia, preferentially initiating tactile allodynia via activation of TRPV1 and TRPA1 on central terminals.…”
Section: Discussionmentioning
confidence: 52%
“…However, increasing data connect TRPA1 to heat sensitivity. In particular, TRPA1 agonists induce heat and mechanical hyperalgesia and a burning pain sensation, but no cold hyperalgesia (Namer et al, 2005;Albin et al, 2008;Merrill et al, 2008;Zanotto et al, 2008;Sawyer et al, 2009;Carstens et al, 2010;Tsagareli et al, 2010;Tsagareli, 2011Tsagareli, , 2013Hoffmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%